An Optimized Protocol for Packaging Pseudotyped Integrase Defective Lentivirus. Issue 1 (December 2016) - Sengupta, Ranjita; Mukherjee, Chandreyee; Sarkar, Nandita; Sun, Zhihong; Lesnik, Jacob; Huang, Joseph; Lu, Biao
Abstract Background A number of integrase defective lentiviral (IDLV) packaging systems have been developed to produce integration deficient lentiviruses for gene delivery and epichromosomal expression. However, despite their growing demand, a comparative study to systemically evaluate the performance efficiency of different mutants on virus packaging and gene expression has not been done. Results Site-directed mutagenesis was used to generate five integrasedeficient mutants for non-integrative lentiviral packaging (NILVP). The five mutants were then individually incorporated to make different integrase defective lentivirus plasmid packaging mix, keeping other packaging factors constant. CD511B-1, a lentivectorexpressing GFP from an EF1 promoter, was packaged with each of the five different lentivirus packaging mix to make pseudotypedviral particles. The performance and packaging efficiency of each of the integrase deficient mutants was evaluated based on GFP expression in HT1080 cells, while the wild type lentivirus packaging mix was used as a control. Of the five integrase mutant candidates, one with the highestGFP transgene expression level was chosen for further characterization. The non-integrative nature of this candidate was confirmed by quantitative polymerase chain reaction and characterized using both dividing and non-dividing cells. Finally, a detailed standard protocol for NILVP using this integrase defective mutant was developed. Conclusions An efficient lentiviral packaging system for producing on-integrative lentivirus was established. This system is compatible with most existing lentivectors and can be used to transduce both dividing and non-dividing cells.